2021
DOI: 10.4308/hjb.29.1.107-113
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Anadara nodifera Shell as Natural Testosterone Booster for Male Canary (Seriunus canaria)

Abstract: Anadara clam shell contains high Zinc. This microelement is recognised as acting natural aromatase blocker (NAB) that capable of boosting testosterone level. The aim of this study was to evaluates the testosterone level of Canaries following Anadara nodifera administration. Adult male Canaries (n = 27) were group into 3 with 9 repetition of each i.e T0 [control, was given by Carboxymethyl Cellulose Sodium (Na-CMC)], T1 (Zinc Sulphate 0.013 mg/30 g BW), and T2 (NAB 0.3 mg/30 g BW). The T2 treatment was NAB or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The Zn contained in BCSP can increase testosterone which further affected the FA, NM, MA, and PCNA-positive cells. These results are in accordance with Yuneldi et al [5] and Astuti et al [19,24], who showed that A. granosa shell powder at 0.9 mg/kg BW, 0.3 mg/30 g BW, and 0.18 mg/200 g BW was capable of increasing the testosterone levels in pelung cockerels, canaries, and rats. According to Li et al [7], the elevation of testosterone can significantly increase the FA, NM, and MA, and according to Taylor et al [51], Mean with different superscripts within the same column are significantly different (p < 0.05).…”
Section: Chest Circumference Pmw Pectoralis Muscle Area Fa Number Of ...supporting
confidence: 91%
See 4 more Smart Citations
“…The Zn contained in BCSP can increase testosterone which further affected the FA, NM, MA, and PCNA-positive cells. These results are in accordance with Yuneldi et al [5] and Astuti et al [19,24], who showed that A. granosa shell powder at 0.9 mg/kg BW, 0.3 mg/30 g BW, and 0.18 mg/200 g BW was capable of increasing the testosterone levels in pelung cockerels, canaries, and rats. According to Li et al [7], the elevation of testosterone can significantly increase the FA, NM, and MA, and according to Taylor et al [51], Mean with different superscripts within the same column are significantly different (p < 0.05).…”
Section: Chest Circumference Pmw Pectoralis Muscle Area Fa Number Of ...supporting
confidence: 91%
“…[ 5 ] and Astuti et al . [ 19 , 24 ], who showed that A. granosa shell powder at 0.9 mg/kg BW, 0.3 mg/30 g BW, and 0.18 mg/200 g BW was capable of increasing the testosterone levels in pelung cockerels, canaries, and rats. According to Li et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations